Pengaruh Kompetensi Pedagogik Dosen Terhadap Motivasi Belajar Mahasiswa Pada Mata Kuliah Statistik Deskriptif Program Studi Ekonomi Islam Jurusan Syariah dan Ekonomi Islam Stain Watampone. - Munawarah, Munawarah (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2018)
This research was design to know the influence of pedagogic to student's motivation. By knowing the influence of pedagogic competence on learning motivation, it is hoped that student's motivation will increase more than before. Motivation is an important thing in learning process, because motivation is abooster for student to do learning activities.Sample of this research is 5th semester student of Watampone which is 50 students. Instruments of data collection in this research are observation, questionnaire and documentation. The regression analysis was simpe-regression analysis. The results showed that there were positive and significant influence of pedagogic competence,  learning motivation in descriptive statistics subject of Islamic Economics of STAIN Watampone